Konsep Keluarga Sakinah Menurut Muhammad Quraish Shihab - Rohmahtus Sholihah; Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
M. Quraysh Shihab is one of the most famous muffasir in Indonesia, he already has many papers such as Tafsir Al Misbah (message, impression and harmony in the Qur'an). He tries to explain about the family that should be known by family members, but if necessary other information that is by the concept of the family sakinah so that the readers understand the purpose of his thoughts. The majority of people want a sick family, but according to M. Quraysh Shihab some of the people do not know about the concept of sakinah family. So he tried to explain through one of his works. Therefore, this study aims to find out about the concept of sakinah family according to M. Quraysh Shihab by islamic teachings. In this literature research, researchers use documentation techniques with philosophical approaches. Through deriftive analytical techniques, researchers discovered the concept of sakinah family presented by M. Quraysh Shihab, first; choosing a life partner, it is emphasized to choose a partner who relies on the one true God. Secondly; households must be based on love, with love carrying out their respective obligations and roles. Third; create a quiet household, to maintain harmony in the family. Keempa; make a good household, to teach good things and can add and preserve what it already has.